Campur Tangan Pemerintah Dalam Pengelolaan Lingkungan: Sebuah Penelusuran Teoretis Berdasarkan Analisis Ekonomi Atas Hukum (Economic Analysis Of Law) - Wibisana, Muhammad Andri Gunawan (UI Scholars Hub, 2017)
Government intervention in environmental management can be considered to fall within CAC instruments. Despite the instruments are the most familiar and practiced, they are criticized since the CAC approach requires too much government intervention. This article observes that government intervention can be justified as an effort to correct market failures. The article also finds that intervention is warranted for some distributive reasons. However, the article also observes possibility that an intervention occurs due to regulatory capture by interest groups, to serve the interest of bureaucrats, or to function as a tollbooth. Indonesian environmental law shows that these CAC instruments still play a major role in environemtal management in Indonesia